Richard Siddoway Bagnall (1884-1962), Entomologist - Louise Berridge (Biodiversity Data Journal, 2023)
This biography describes the life and professional work of entomologist and industrialist Richard Siddoway Bagnall (1884-1962). This work significantly expands on the biographical notes of Laurence Mound in his paper “A review of R. S. Bagnall’s Thysanoptera Collections”.Bagnall’s life and entomological career is described in detail, including a clarification of his birth date. This biography was written to complement the recent digitisation of Bagnall’s Thysanoptera slides at The Natural History Museum, London, and it is hoped that this biography will be of benefit to future workers upon his material. In addition to Thysanoptera, Bagnall also worked on Collembola, Coleoptera, Myriapoda and other groups.